Les « saints voyages » du Père Beurrier, entre mission et pèlerinage - Isabelle Brian (L'Atelier du CRH)
The Sainte-Geneviève library holds the memoirs of Fr Paul Beurrier, a canon regular who had a long career. An active member of the reform within his order, of the Catholic Reformation and the Counter-Reformation, he was led by his functions to travel frequently. Compared to some of his contemporaries, however, he was neither a great traveler nor a true pilgrim. The interest of his writings lies above all in the retrospective view he takes of his travels. His memoirs tell us about the extent, frequency and material conditions of his journeys, which he usually made on horseback. In a form of dramatisation, he also related the dangers of the road and the stages. But above all, travel was an opportunity for him to experience divine protection through a world full of signs, transforming the narrative into a form of thanksgiving.